1993
DOI: 10.1016/0370-2693(93)90333-d
|View full text |Cite
|
Sign up to set email alerts
|

Lattice topological field theory and first order phase transition

Abstract: Carrying out perturbations around a lattice topological field theory in two dimensions, we show that it is on a first order phase transition fixed point with multiplicity n(n − 1)/2, where n is the number of its independent physical observables. We discuss about the order parameters and the finite size effect for the free energy. The finite size effect is described by the topological field theory. We investigate also the renormalization group flow near the fixed point, and show that the flow agrees with that o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1995
1995
1995
1995

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…TLFTs are special cases of general lattice field theories, the investigation of the positions of TLFTs in the parameter space of general lattice field theories will clarify the specialties of TFTs and the background reason of their appearances in the investigations of quantum gravity and string theory. The present author investigated the phase structure around 2D TLFTs by a perturbative scheme and found that they are in general on multiple first order phase transition points [37] .…”
Section: Introductionmentioning
confidence: 98%
“…TLFTs are special cases of general lattice field theories, the investigation of the positions of TLFTs in the parameter space of general lattice field theories will clarify the specialties of TFTs and the background reason of their appearances in the investigations of quantum gravity and string theory. The present author investigated the phase structure around 2D TLFTs by a perturbative scheme and found that they are in general on multiple first order phase transition points [37] .…”
Section: Introductionmentioning
confidence: 98%